Pengaruh Model Pembelajaran Reading Questioning Answering (RQA) Untuk Meningkatkan Keaktifan Belajar IPA Siswa SMP - Harwandini, Ita; Yulianti, Pratiwi Try; Firdausy, Julia Esa Ayu; Wahyuni, Sri; Yusmar, Firdha; Nuha, Ulin (Peneliti.net, 2024)
The low reading interest and activeness of students at school, as well as the lack of students' ability to apply the knowledge gained is one of the factors that causes teachers to apply learning models that can increase student activity and learning outcomes. One of the learning models based on constructivism learning theory is the Reading, Questioning, and Answering (RQA) learning model. The center of this learning model is students constructing their own knowledge, so this is likely to cause students to become more active in class. This is the background for researchers to conduct research on the Reading Questioning and Answering (RQA) learning model. This study aims to determine the effect of the Reading Questioning and Answering (RQA) model in learning to increase students' activeness and science learning outcomes in junior high school. The method used in this research is literature review by analyzing 10 previous literatures related to this research. Based on the 10 previous literatures, the results obtained were that the Reading Questioning and Answering learning model had a positive effect on increasing the activity and learning outcomes of junior high school students in science